Potent carbonic anhydrase I, II, IX and XII inhibition activity of novel primary benzenesulfonamides incorporating bis-ureido moieties - Tuba Tekeli; Suleyman Akocak; Andrea Petreni; Nebih Lolak; Servet Çete; Claudiu T. Supuran (Taylor & Francis Group, 2023)
A novel series of twelve aromatic bis-ureido-substituted benzenesulfonamides was synthesised by conjugation of aromatic aminobenzenesulfonamides with aromatic bis-isocyanates. The obtained bis-ureido-substituted derivatives were tested against four selected human carbonic anhydrase isoforms (hCA I, hCA II, hCA IX and hCA XII). Most of the new compounds showed an effective inhibitory profile against isoforms hCA IX and hCA XII, also having some selectivity with respect to hCA I and hCA II. The inhibition constants of these compounds against isoforms hCA IX and XII were in the range of 6.73-835 and 5.02-429 nM, respectively. Since hCA IX and hCA XII are important drug targets for anti-cancer/anti-metastatic drugs, these effective inhibitors reported here may be considered of interest for cancer related studies in which these enzymes are involved.